The interactive effects of corruption and institutional quality on economic performance - Azuka Elvis Ozegbe; Ikechukwu Kelikume (International Journal of Management, Economics and Social Sciences (IJMESS), 2022)
This study was motivated by the quest to investigate how the interaction between corruption and institutional quality affects Nigeria's economic performance by testing the validity of the "sand the wheels" and "grease the wheels" corruption hypothesis through the Barro-type endogenous growth model from the Nigerian perspective which has been ignored by extant studies. Annual time series data obtained from the World Development Indicators (WDI), the Transparency International(TI),and the Central Bank of Nigeria (CBN) from 1970 to 2020 were used to conduct the study's analysis. The study employed the Autoregressive Distributed Lag (ARDL) approach to determine the interactive effects of corruption and institutional quality on economic performance. The study revealed that corruption-institutional quality interaction exerts a negative and significant impact on economic performance. This supports the assertion that institutional quality in Nigeria is feeble and overwhelmed by the magnitude of corruption and the level of individual influences. The trajectory of Nigeria's economic performance is impeded by high level of corruption and weak institutional quality. Therefore, it is imperative for policy interventions to focus on tackling the incidence of corruption, improving institutional qualities which would have ripple positive effects on Nigeria's economic performance.
Keywords: C10; H10; K10; 330; Corruption; institutional quality; economic performance; endogenous growth model; Autoregressive Distributed Lag (ARDL)